The Effect of Competence, Transactional Leadership Style, and Organizational Culture on Business Sustainability, With Employee Performance as a Mediating Variable, at Mercu Buana University - Mardiyah Noviana; Tine Yuliantini (International Journal Labs, 2026)
This study is motivated by the increasing challenges faced by higher education institutions in maintaining business sustainability amid global competition, technological transformation, and declining student enrollment. Human resource quality, leadership style, and organizational culture are considered important factors in supporting institutional sustainability through improved employee performance. Therefore, this study aims to analyze the influence of competence, transactional leadership style, and organizational culture on business sustainability, with employee performance serving as a mediating variable at Mercu Buana University. This research employed a quantitative approach using a causal research design. Data were collected from 218 lecturers and educational staff selected through stratified random sampling. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0 software. The findings revealed that competence, transactional leadership style, and organizational culture positively and significantly affect employee performance and business sustainability. Employee performance also significantly influences business sustainability and successfully mediates the relationship between the independent variables and sustainability. Organizational culture emerged as the strongest predictor of business sustainability. The study concludes that strengthening employee competencies, implementing effective transactional leadership, and developing a collaborative organizational culture are essential strategies for improving employee performance and ensuring the long-term sustainability of higher education institutions.